Interactive PCB layout design system for EMC/EMI minimisation - Han, Yi. (2010)
Most current printed circuit board (PCB) place and routing tools are used to accelerate the placement and routing tasks in PCB design. However, a major weakness in PCB software is the failure to account for electromagnetic interference (EMI) problems. To overcome this, a human expert is thus required to layout the PCB manually. To be effective, PCB layout software must be able to account for electromagnetic compatibility (EMC) requirements. The purpose of the study is to replace human expert by incorporating artificial intelligence (AI) into the existing PCB layout software with the aim to minimize possible EMI problems in design of PCBs. This is done by using the customized Integration Menu to integrate the developed add-on modules (Circuit Recognition, Circuit Partition, Board Partition, Component Placement, Knowledge-base( 1) for Placement, Knowledge-base(2) for Routing) and the existing Mentor Graphics Board Station PCB system to form the PCBDEMC system.